Study of the factors reluctant of good agricultural practices application among paddy farmers / Amirul Nasrin Abdul Halim - Abdul Halim, Amirul Nasrin (Faculty of Plantation and Agrotechnology, 2019)
Paddy or Oryza sativa is very important in Asian countries because almost people consume rice as their daily food and in order to improve yield productivity Ministry of Agriculture and Agro-based Industry was launched MyGAP. Malaysia Good Agricultural Practices is food safety and quality standards in plantation by set a regulation to produce good environmentally friendly and socially-acceptable product. However, yield and income of paddy farmers is still do not achieve the desired goals because certain farmers are reluctant the GAP. The objective of this study is to determine factors reluctant of GAP application among paddy farmers, to identify the most factors chosen by the farmers reluctant GAP application and to determine the relationship between factors and yield productivity. This study was carried out in Tengah Padang, Sempang and Pengkalan in Merlimau, Melaka. The simple random sampling was used to choose paddy farmers as respondents and almost 59 sample size were selected out of 71 populations. The descriptive analysis, correlation regression and multiple regressions were used to analyse the data. The result was found that a quality product, management, cost and knowledge have a positive relationship between the factors reluctant of GAP with a yield of paddy farmers. For multiple regression, the result showed of knowledge is the most influential factor reluctant of GAP application among paddy farmers.